2021
DOI: 10.1186/s12920-020-00849-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying of 22q11.2 variations in Chinese patients with development delay

Abstract: Background 22q11.2 variation is a significant genetic factor relating to development delay and/or intellectual disability. However, the prevalence, genetic characteristics and clinical phenotype in Chinese patients are unknown. Methods In total 6034 patients with development delay and/or intellectual disability were screened by multiplex ligation-dependent probe amplification (MLPA) P245 and G-band karyotyping. The positive patients with 22q11.2 im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
4
8
0
Order By: Relevance
“…This indicated that SNAP29 is essential for male fertility and spermatogenesis [ 45 ]. Other study also indicated that patients with typical LCR22 A-D deletions may present with cryptorchidism [ 46 ]. Furthermore, fetal loss or infant death is a rare symptom in patients with 22q11.2DS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that SNAP29 is essential for male fertility and spermatogenesis [ 45 ]. Other study also indicated that patients with typical LCR22 A-D deletions may present with cryptorchidism [ 46 ]. Furthermore, fetal loss or infant death is a rare symptom in patients with 22q11.2DS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…MLPA assay was carried out in accordance with the manufacturer’s instructions. The SALSA P245 probe mix (MRC-Holland, Netherlands) was used to screen for microdeletion/microduplication syndromes as previously described [ 5 ]. The SALSA P371 probe mix (MRC-Holland, Netherlands), which encompasses more probes specific for the chromosome 15q24 region, was used to confirm the deletion and infer the deletion size.…”
Section: Methodsmentioning
confidence: 99%
“…MLPA assay and the subsequent results analyses were performed as previously described [ 12 ]. Briefly, The SALSA MLPA KIT P245 (MRC Holland, Amsterdam, Netherlands) were used for MLPA analysis according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional chromosome G-band karyotyping analysis of the cultures of peripheral blood and amniotic fluid blood cells was performed as previously described [ 12 ]. Leica CytoVision (Leica, USA) was used to capture images of mitotic metaphase chromosomes.…”
Section: Methodsmentioning
confidence: 99%